[PP.15.05] HEMODYNAMICS DETERMINANTS OF THE SHORT-TERM BLOOD PRESSURE VARIABILITY ACCORDING TO THE WAVE TRANSMISSION AND RESERVOIR PRESSURE THEORIES. (September 2016) - Chen, C.; Hsu, P.; Cheng, H.; Sung, S.; Chuang, S.; Lakatta, E.; Yin, F.; Chou, P.
Abstract : Objective: A high short-term blood pressure variability (BPV) can predict long-term cardiovascular mortality independently of 24-hour systolic blood pressure (24-h SBP). The present study aimed to investigate the hemodynamics determinants of BPV according to models of wave transmission and reservoir pressure. Design and method: A cohort of 624 normotensive and 633 untreated hypertensive Taiwanese participants (overall 669 men, aged 30–79 years) with complete base-line ambulatory blood pressure monitoring and hemodynamics study was drawn from a community-based survey. BPV was assessed by calculating the read-to-read average real variability of the 24-h diastolic blood pressure (ARVd). The wave transmission variables included carotid-femoral pulse wave velocity (cfPWV), amplitudes of the forward (Pf) and backward (Pb) pressure waves from the decomposed carotid pressure waveforms. The reservoir pressure variables included peak (PRP), amplitude (PRA), and integral (PRI), and excess pressure integral (XPRI) of the reservoir pressure model. Results: ARVd and 24-h SBP were significantly correlated with age, body mass index, and all wave-transmission and reservoir pressure variables. Based on the wave transmission model and multi-variable regression analysis, Pb, Pf, and cfPWV were significant independent determinants of ARVd (model r2 = 0.22) and 24-h SBP (model r2 = 0.535), when age, sex, body mass index, heart rate, and total peripheral resistance were accounted for. Based on the reservoir pressure model, the significant independent determinants were PRP and PRI for AVRd (model r2 = 0.22) and all 4 variables (PRP, PRA, PRI, and XPRI) for 24-h SBP (model r2 = 0.709). The model r2 for ARVd did not improve appreciably when 24-h SBP was also added to the models (model r2 = 0.224 and 0.231, for the wave transmission and reservoir pressure models, respectively). Conclusions: Unlike 24-h SBP, BPV is only partially influenced by the hemodynamics variables and is likely mainly determined by other non-hemodynamics factors.